Discontinuous yielding phenomena triggered by Zn addition in low-alloyed Mg-Al-Ca-Mn alloys. (December 2022) - Li, Z.H.; Gao, S.; Sasaki, T.T.; Nakata, T.; Kamado, S.; Tsuji, N.; Hono, K.
Abstract: Clarifying the origin of the yielding phenomenon is essential for preventing the deterioration of the flow stability and surface finish of magnesium alloy sheet products. This study reports the effect of Zn addition on discontinuous yielding in Mg-1.2Al-0.5Ca based low-alloyed magnesium alloy sheets. Digital image correlation strain mapping shows that the Lüders deformation after a yield-drop is a distinct phenomenon that only occurs in the Zn-containing sample. Correlative transmission electron microscopy and atom probe tomography analysis revealed the segregation of Ca-Zn co-clusters to dislocations after 3% strain, indicating that dislocation locking by the Ca-Zn co-clusters caused the yield-drop. Stretching the sheet along the transverse direction causes as twice as much Lüders strain as stretching it along the rolling direction. Correlative electron backscattered diffraction and transmission electron microscope analysis implies that the significant activation of non-basal 〈 a 〉 slip may suppress Lüders deformation. Graphical abstract: Image, graphical abstract